Basic statistics for business & economics - Lind, Douglas A. (The McGraw-Hill/Irwin series Operations and decision sciences, 2011)
What is statistics; Describing data: frequency tables, frequency distributions, and graphic presentation; Describing data: numerical measures; Describing data: displaying and exploring data; A survey of probability distributions...